2018
DOI: 10.1021/acs.chemmater.8b02359
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Heteroatoms in Conjugated Polymers Backbone toward Air-Stable, High-Performance n-Channel Unencapsulated Polymer Transistors

Abstract: Organic field-effect transistors (OFETs) without any encapsulation of polymer semiconductor layers that still exhibit unipolar n-type characteristics under air conditions are very rare. In this study, we use fluorinated bithiophene as a donor, and bis(2oxoindolin-3-ylidene)-benzodifuran-dione (BIBDF, P1) and azasubstituted BIBDF (P2) as acceptor units to develop air-stable and unipolar electron transport polymer semiconductors. Unencapsulated OFETs based on P1 and P2 were fabricated and directly evaluated unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 49 publications
(110 reference statements)
1
67
0
Order By: Relevance
“…[9,21] More importantly,the devices showed comparable performances even when measured in air (Figures 4c,d,g,h, Table 2). [22] The excellent air-stability of P2-based devices was most probably caused by the deep E LUMO of À4.00 eV. This result is remarkable,c onsidering that the organic layer was exposed to air in the case of the TC/BG device configurations and the air-stability of the n-type materials is generally poor.…”
Section: Forschungsartikelmentioning
confidence: 99%
See 2 more Smart Citations
“…[9,21] More importantly,the devices showed comparable performances even when measured in air (Figures 4c,d,g,h, Table 2). [22] The excellent air-stability of P2-based devices was most probably caused by the deep E LUMO of À4.00 eV. This result is remarkable,c onsidering that the organic layer was exposed to air in the case of the TC/BG device configurations and the air-stability of the n-type materials is generally poor.…”
Section: Forschungsartikelmentioning
confidence: 99%
“…[22] Choi et al proposed ameasurement reliability factor g to gauge the reliability of the reported values. [22] Choi et al proposed ameasurement reliability factor g to gauge the reliability of the reported values.…”
Section: Forschungsartikelmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 21,22 ] The introduction of strongly electronegative fluorine groups has been shown to be an effective strategy for stabilizing the LUMO levels. [ 23–26 ] Owing to the small van der Waals radius, fluorination is highly attractive as these benefits can usually be achieved without disruption to backbone planarity from the introduction of undesired steric clashes. In addition, fluorination often helps to promote inter‐ and intramolecular interactions via a range of noncovalent interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Many articles report the synthesis of the novel organic molecules or polymers with highly active chromophores and superior optical activity, as response to the demand of substances with NLO properties for various applications [83][84][85][86].…”
Section: Introductionmentioning
confidence: 99%